2008
DOI: 10.1016/j.pupt.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium improves FEV1 in patients with COPD irrespective of smoking status

Abstract: This study evaluated whether the effect of tiotropium on the change in trough forced expiratory volume in 1 s (FEV 1 ), vs. placebo, is affected by smoking status. In a 3-month, double-blind study in 31 centres in Portugal, 311 (289 completed) patients were randomised to tiotropium 18 mg once daily or placebo. Baseline mean (standard deviation (SD)) FEV 1 was 1.11 (0.39) l in the tiotropium group and 1.13 (0.39) l in the placebo group. Patients had an average smoking history of 55 (25.7) pack-years; 80 (26%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
(21 reference statements)
4
24
0
3
Order By: Relevance
“…Conversely, tiotropium was associated with consistently significant improvements in lung function compared to the control arm over the course of the 4-yr study in all smoking behaviour categories, except for a more modest and nonsignificant improvement in post-bronchodilator FEV1 in the intermittent smokers at 4 yrs. Interestingly, consistent with the earlier findings of MOITA et al [1], the tiotropium-related improvement FEV1 was numerically greater in the continuing smokers than the ex-smokers at trough and even more so when examined after the administration of study drug and four inhalations of albuterol and ipratropium (table 3). However, the results of the study by MOITA et al [1] may not necessarily be comparable with the results of the UPLIFT trials due to possible differences in the proportion of subjects using concomitant medications in the two studies.…”
Section: Copd and Smoking-related Disorders Dp Tashkin Et Alsupporting
confidence: 89%
See 2 more Smart Citations
“…Conversely, tiotropium was associated with consistently significant improvements in lung function compared to the control arm over the course of the 4-yr study in all smoking behaviour categories, except for a more modest and nonsignificant improvement in post-bronchodilator FEV1 in the intermittent smokers at 4 yrs. Interestingly, consistent with the earlier findings of MOITA et al [1], the tiotropium-related improvement FEV1 was numerically greater in the continuing smokers than the ex-smokers at trough and even more so when examined after the administration of study drug and four inhalations of albuterol and ipratropium (table 3). However, the results of the study by MOITA et al [1] may not necessarily be comparable with the results of the UPLIFT trials due to possible differences in the proportion of subjects using concomitant medications in the two studies.…”
Section: Copd and Smoking-related Disorders Dp Tashkin Et Alsupporting
confidence: 89%
“…The sparse publications that have addressed this issue are mainly limited to short-term, 3-month studies involving anticholinergic bronchodilators and have yielded somewhat conflicting findings, as described above [1,2]; one of these studies showed a substantially, although not significantly, greater numerical response to tiotropium in trough FEV1 in continuing smokers than ex-smokers [1], while the other showed a more marked trough FEV1 response to ipratropium in ex-smokers than current smokers [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial was a prospective, multicentre, randomized, double-blind, placebo-controlled parallel-group study designed to determine whether the effect on lung function of inhaled tiotropium 18 g once daily over 12 weeks was affected by smoking status, 4 where thirty-one Portuguese respiratory centres participated. The trial was approved by each local ethics committee and institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Тиотропий обладает обширной доказательной базой в лечении больных ХОБЛ. Тиотропий оказывает количественно боль шее влияние на показатели спирометрии у курящих больных ХОБЛ, чем у бывших курильщиков [33]. В случае БА ипратропий также оказался более эф фективным именно у курящих пациентов [34].…”
Section: курениеunclassified